The Relationship between Neutrophil Lymphocyte Ratio in Head Injured Patients and Patient Outcomes - Hidayat, Ahmad; Sentosa, Alwi (Sriwijaya Journal of Neurology, 2023)
Introduction: Head injury causes microglial activation and release of proinflammatory cytokines. One of the inflammatory markers that can be used is the neutrophils to lymphocytes ratio (NLR). Within 24 hours after brain injury, the number of circulating neutrophils was markedly increased compared to the uninjured control group. This study aimed to determine the relationship between ratios of neutrophil-lymphocyte head injury patients with patient outcomes at Dr. M Djamil General Hospital, Padang, Indonesia. Methods: This study was a cross-sectional analytic observational study. A total of 36 research subjects participated in this study. Observations on sociodemographic, clinical, and laboratory data were carried out in this study. Data analysis was carried out using SPSS using univariate and bivariate. Results: The majority of study subjects with a good Glasgow outcome scale had a neutrophil-lymphocyte ratio <7.35. Meanwhile, research subjects with Glasgow the poor outcome scale had a neutrophil-lymphocyte ratio ≥7.35, p<0.05. Conclusion: There is a relationship between the neutrophil-lymphocyte ratio and the outcome of head injury patients at Dr. M Djamil General Hospital, Padang, Indonesia.